Proton beam range and charge verification using multilayer faraday collector - Yeap, Ping Lin (2024)
A daily quality assurance (QA) check in proton therapy is ensuring that the range of each proton beam energy in water is accurate to 1 mm. This is important for ensuring that the tumor is adequately irradiated while minimizing damage to surrounding healthy tissue. It is also important to verify the total charge collected against the beam model. This work proposes a time-efficient method for verifying the range and total charge of proton beams at different energies using a multilayer Faraday collector (MLFC).